2015
DOI: 10.1177/0394632015590948
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of resistance to low pH and bile salts of human Lactobacillus spp. isolates

Abstract: There are nearly 100 trillion bacteria in the intestine that together form the intestinal microbiota. They are 'good' bacteria because they help to maintain a physiological balance and are called probiotics. Probiotics must have some important characteristics: be safe for humans, be resistant to the low pH in the stomach, as well as bile salts and pancreatic juice. Indeed, their survival is the most important factor, so that they can arrive alive in the intestine and are able to form colonies, at least tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…As the probiotic supplement is going to be administered orally, the bacterial constituents should be resistant to the conditions of the gastrointestinal tract (GIT). Moreover, the number of live organisms that reach the gut should be large enough to produce their beneficial effect on the host [9]. On the other hand, LAB can be reservoirs of resistance genes, which could be transferred to other bacteria and even to human pathogens [10], which is why some of their safety-related characteristics should be studied.…”
Section: Introductionmentioning
confidence: 99%
“…As the probiotic supplement is going to be administered orally, the bacterial constituents should be resistant to the conditions of the gastrointestinal tract (GIT). Moreover, the number of live organisms that reach the gut should be large enough to produce their beneficial effect on the host [9]. On the other hand, LAB can be reservoirs of resistance genes, which could be transferred to other bacteria and even to human pathogens [10], which is why some of their safety-related characteristics should be studied.…”
Section: Introductionmentioning
confidence: 99%
“…identification is a valid example of highly related bacterial species that require such approach that provides the polyphasic analysis of two distinct phylogenetic markers: the 16S rDNA gene and the tuf gene encoding for the elongation factor Tu (EF-Tu). [16][17][18]33 Seven products tested in this study showed levels of viable counts similar to or slightly higher than the label claim until 3 months to deadline. The viable bacteria, recognized in two vaginal products without indication, were acceptable.…”
Section: Discussionmentioning
confidence: 91%
“…In this scenario, the polyphasic taxonomy suggested by Vandamme et al 31 and by other authors, 17,18,32 is the better choice for bacterial identification.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations